Draft precis of evidence to be given before the Departmental Committee on Midwives
1928-09 1928 1920s 6 pages 6. 26. The midwife has had to do work of a very highly responsible kind and we believe that our proposals make an enormous difference in reducing maternal mortality and improving the health both of mother and baby. It cannot be done without cost, but it would be a very small cost in comparison with the national loss due to the present inadequate provision. We are constantly told that women's service to the nation is of incalculable value, and we think that the nation can well afford to make the risks of death and ill health as small as possible. 292/824/1/116